Innovation in Compensation Payments: What Does the Future Hold for Compensation in Cryptocurrency? - Ruksana, Ashraf; Mavoothu, Duraipandi; Mathew, Vineetha; Nimmi, P M; Renjith, K R (Journal of Telecommunications and the Digital Economy, 2024)
The growing economic influence of cryptocurrency and the development of the associated infrastructure has brought about an interest in the new areas of its application. Payment of compensation in cryptocurrency is one such evolving application of cryptocurrency. Using a qualitative research design, we attempt to identify the factors and ecosystem constituents that play an important role in the diffusion, adoption and use of cryptocurrency as a compensation medium. A hybrid methodology involving both inductive and deductive methods of qualitative inquiry was used to develop the themes. The study identified nine main factors that influenced a participant’s decision to accept compensation in cryptocurrency. They are: (1) the prospects of high return; (2) ease of transaction; (3) faster international transactions; (4) price volatility of cryptocurrencies; (5) threat of hacking; (6) taxation policies of the country; (7) lack of recognition as legal tender; (8) influence of peer groups; and (9) influence of celebrities. The inductive part of the study enabled the mapping of the major stakeholders involved in the decision, namely, the government, the employer, the peer groups of the employee, celebrities and the cryptocurrency-issuing company.